Kyphoplasty of C2 Pathological Fractures Using an Anterior Midline Approach and Steerable Osteotome: Technical Note and Case Series. Issue 6 (19th December 2022) - Krafft, Paul R.; Peto, Ivo; Flores-Milan, Gabriel; Reeves, Corey; Klein, Sierra; Alikhani, Puya; Tran, Nam D.
Abstract : BACKGROUND: Malignant lesions involving the C2 vertebral body (axis) may be challenging to treat, and not all patients with cancer are good candidates for posterior cervical or occipitocervical instrumentation. OBJECTIVE: To describe a modified technique of the direct anterolateral C2 kyphoplasty using a steerable osteotome, commonly used for the treatment of thoracolumbar spinal lesions. We also report a case series of 11 patients treated with this technique at our institution. METHODS: The authors performed a retrospective review of all patients who underwent a C2 kyphoplasty using the anterior midline approach from 2010 to 2020. Patient demographics, tumor characteristics, pain severity (visual analog scale), Karnofsky performance status, perioperative complications, and postoperative spinal stability were assessed. RESULTS: The main indication for a C2 kyphoplasty was refractory neck pain. All patients tolerated the procedure well. There were no intraoperative complications. One patient developed transient dysphagia. Visual analog scale scores were 9.00 ± 1.10 preoperative and 3.73 ± 1.85 at 2 weeks and 1.67 ± 1.66 at 3 months after the procedure and continued to stay low during the remainder of the follow-up (4-60 months). The Karnofsky performance status improved from 72.73 ± 11.04 preoperatively to 82.22 ± 8.33 at 2 weeks and 86.67 ± 5.00 at 3 months after the procedure. There was no evidence of new occurrence or progression of C2 fractures. CONCLUSION: The anterior kyphoplasty using a steerable osteotome for tumors of the axis can result in lasting pain reduction and improved cervical stability while demonstrating a low complication rate.